(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The generalization of data of pollen paleopalynological studies are provided. This research was didicated to the pollen of the family Lamiaceae as part of palynological characteristics of recent surface soil samples and deposits of the Pleistocene-Holocene of the plain part of Ukraine. It has been established that in the fossil condition pollen of Lamiaceae was identified to the level of family. Very rarely pollen grains in the fossil palinofloras are defined to the genus and species levels. The article presents the results of species-level identification of Origanum vulgare pollen grains in the composition of palynological characteristics on Holocene deposits in 10 sections of the Forest, Forest-Steppe and Steppe zones of Ukraine. For the first time, the spatiotemporal differentiation of distribution patterns of O. vulgare in the Holocene was justified and reconstructed using generalized materials of integral paleofloristic and radiocarbon studies. Pollen morphology of O. vulgare was studied using light and scanning electron microscopy. Pollen grains are 6-colpate, ellipsoidal or oblate-spheroidal, occasionally spheroidal; medium-sized. Their outline in equatorial view is elliptical, rarely circular, in polar view 6-lobate. Colpi are almost identical in length, narrow, with distinct margins and more or less acute ends. The four mesocolpi are generally narrower, and the other two are wider. Exine sculpture is distinct, bireticulate, colpus membrane psilate-granulate. Diagnostic characters of O. vulgare pollen are reported. It is demonstrated that the diagnostic characters of pollen grains can be used for more accurate identification of fossil pollen grains to the species level for pollen analysis in Pleistocene-Holocene deposits of Ukraine and adjacent areas.